Midlife insulin resistance, APOE genotype, and change in late-life brain beta-amyloid accumulation : A 5-year follow-up [11C]PIB-PET study - Pietilä, Elina (Elsevier, 2025)
We studied if midlife insulin resistance (IR) and APOE genotype would predict brain beta-amyloid (Aβ) accumulation and Aβ change in late-life in 5-year follow-up [11C]PIB-PET study. 43 dementia-free participants were scanned twice with [11C]PIB-PET in their late-life (mean age at follow-up 75.4 years). Participants were recruited from the Finnish Health2000 study according to their HOMA-IR values measured in midlife (mean age at midlife 55.4 years; IR+ group, HOMA-IR > 2.17; IR− group, HOMA-IR <1.25), and their APOEε4 genotype. At late-life follow-up, [11C]PIB-PET composite SUVr was significantly higher in IR+ group than IR− group (median 2.3 (interquartile range 1.7–3.3) vs. 1.7 (1.5–2.4), p = 0.03). There was no difference between IR- and IR+ groups in [11C]PIB-PET SUVr 5-year change, but the change was significantly higher in IR+/APOEε4+ group (median change 0.8 (0.60–1.0)) than in IR−/APOEε4− (0.28 (0.14–0.47), p = 0.02) and in IR+/APOEε4− group (0.24 (0.06–0.40), p = 0.046). These results suggest that APOEε4 carriers with midlife IR are at increased risk for late-life Aβ accumulation.